Impact of discontinuation of cephazolin prophylaxis on the incidence of postoperative adverse events in cataract surgery - Kazutaka Uchida; Keita Takahama; Kenshiro Higashi; Yuki Kusano; Koki Matsumoto; Yoshihiro Nakagawa; Kazutaka Oda (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Cataract surgeries are increasing annually, making appropriate medical management essential. The routine use of systemic antimicrobial agents for preventing surgical site infections lacks strong evidence and may increase the risk of drug-resistant bacteria and adverse events. This study examined the impact of discontinuing cefazolin (CEZ) administration during the perioperative period of cataract surgery on the incidence of postoperative adverse events and medical costs. Methods Inpatient cataract surgery patients were divided into two groups: the CEZ-use group (April 2021 to March 2022) and the non-CEZ-use group (April 2022 to March 2023). The primary endpoints were the incidence of adverse events and medical costs, while the secondary endpoint was the incidence of endophthalmitis. Results A total of 265 patients were in the CEZ group, and 316 were in the non-CEZ group. Six postoperative adverse events (2.3%, 95% confidence interval: 0.8–4.9) occurred in the CEZ group, with an estimated 230 patients (80–490 from the 95% confidence interval) expected to experience adverse events per 10,000 patients using CEZ. The non-CEZ group had no adverse events and reduced drug costs by approximately 46,000 yen. Insurance claim amounts were also reduced. No cases of early postoperative endophthalmitis were observed in either group. Conclusions Discontinuation of CEZ prophylaxis during the perioperative period of cataract surgery effectively reduced the risk of adverse events. Medical for the period after discontinuing CEZ did not increase. Trial registration Retrospectively registered.